Religious and Cultural Values In The Mapacci Traditional Of The Bugis Indigenous Community - Indatono, Pulung Revastianto; Rodiah, Ita; Aminah, Siti (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
The Mappacci ritual contains various symbols related to identity and social status. This process involves a series of actions that aim to physically cleanse the bride and groom and prepare them mentally and spiritually to enter a new phase in their lives. Thus, this study provide deeper insight into how the Bugis community interprets marriage as a sacred institution entirely of responsibility. This research investigates the Mappacci procession, comprehensively including the procedures, the roles of the actors, and the symbolic meaning of each stage of the ritual, along with their relationship to the belief system and social structure of the Bugis tribe. The method employed is a type of field research with a qualitative approach, observations, interviews, and documentation for data collection. Descriptive data analysis techniques are also used. The results of the research show that religious values are found in the Mappacci tradition, namely in the Mappasau Botting procession (taking care of the bride), the Cimme Passilli procession (bathing the bride), and Mappanre Temme (completing the recitation of the Qur'an). In addition, the cultural value in the Mappacci tradition lies in the tools or objects used in the Bugis traditional Mappacci process area, which contain meaning and messages, namely head pillows, Bugis sarongs/silk sarongs, banana leaf shoots, jackfruit leaves, pacci leaves, jasmine rice, candles, brown sugar, coconut, and pacci holders or containers